Kajian Pengembangan Ekowisata Bahari Sebagai Mata Pencaharian Alternatif Bagi Masyarakat Tulamben dan Amed Kabupaten Karangasem Propinsi Bali - I Gede Made Subagiana; Sagung Mas Suryaniadi; Ni Luh Made Wijayati (P3M Politeknik Negeri Bali, 2019)
Developing marine eco-tourism as an alternative source of livelihood. To accelerate poverty alleviation in Karangasem regency, where 6.88% of the population of 27,800 people are classified as poor , various efforts have been made by the Regional Government such as developing marine eco-tourism in Tulamben Village, Kubu Sub-district and Amed Village, Abang District of Karangasem Regency. Developing of marine eco-tourism resulted in a shift in livelihood patterns of the population from the agricultural sector to the tourism industry sector. The problem in this research is